siRNA-mediated downregulation of TC21 sensitizes esophageal cancer cells to cisplatin - Hasan, Md. Raghibul (Baishideng Publishing Group Co., Limited, 2012)
AIM: To determine the functional significance of TC21 in esophageal squamous cell carcinoma (ESCC). METHODS: TC21 siRNA transfection was carried out using Hyperfectamine to knock down TC21, and transcripts were analyzed by reverse transcription-polymerase chain reaction and protein by Western blotting. We demonstrated the effect of TC21 downregulation of cell signaling in esophageal cancer cells by assessing the phosphorylation status of its downstream targets, phosphoinositide 3-kinase (PI3K), phosphatase and tensin homolog (PTEN), protein kinase B (pAkt), nuclear factor-κB (NF-κB) and cyclinD1 using specific antibodies. Cell survival analysis after cisplatin treatment was carried out by cell viability assay and cell cycle analysis using flow cytometry. RESULTS: TC21 knockdown in human ESCC cell line TE13 cells, showed only a marginal increase (14.2%) in cell death compared with control cells. The expressions of the signaling proteins PI3K and pAkt, transcription factor NF-κB, and cell cycle protein cyclin D1 were markedly decreased in response to TC21 downregulation, whereas the level of pPTEN, an antagonist of PI3K, was increased. In addition, we evaluated the potential of TC21 as a putative target for sensitizing ESCC cells to the chemotherapeutic agent cisplatin. Increased cell death (38.4%) was observed in cells treated with cisplatin after TC21 knockdown compared with cells which were treated with cisplatin alone (20% cell death). CONCLUSION: Results suggest that TC21 mediates its effects via the PI3K-Akt pathway, NF-κB and cyclin D1, and enhances chemoresistance in esophageal cancer cells.